The Implementation of Hadits on Dzikir and Ihsan: a Living Hadith Study on the Manaqiban Tradition in Majelis Dzikir Al-Khidmah Lampung - Muhamad Nasrudin; Digdo Aji Mukti; Ahmad Nashirudin; Ibnu Akbar Maliki (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Al-Khidmah is a council of dzikir in which the congregations consist of various educational, economic, and social backgrounds. Uniquely, in the council, there are people who have criminal backgrounds such as drug addicts and thugs. In its development, these people experienced a change in character towards ihsan. This change is suspected to be the impact of their participation in Majelis Dzikir Al-Khidmah of dzikir. This paper examines the living hadith about dzikir and ihsan in Al-Khidmah and it’s role in shaping the character of its congregations towards ihsan. This paper was a field research in Simbarwaringin, Trimurjo sub-district, Central Lampung. This was a qualitative descriptive paper that provides a description of the living hadith and the formation of ihsan characters in Al-Khidmah Lampung. This paper was conducted by using participation method with the symbolic interaction method. The results concluded that Al-Khidmah revived the values of hadith about ihsan in three forms of tradition: practice, oral, and written. The character of the ihsan is measured by using the parameters of the asas al khomsa contained in the interaction model, the relation model, and the ritual dzikir of manaqib. This paper adds the treasure of the hadith study about the practice of hadith to form the character of ihsan through tarekat